Transformation of Stigma into Opportunity: A Qualitative Study of Coaching Strategies for Female Inmates at Class IIA Kerobokan Prison, Bali - MIRA VERANITA; Ade Sudrajat; Dyah Bayu Framesthi; R. Raya Mustiraya (JURNAL PENDIDIKAN, HUMANIORA, LINGUISTIK DAN SOSIAL (JAGADDHITA), 2026)
The correctional system and the process of social reintegration still face social stigma toward women who come into conflict with the law. Female inmates face layered stigma because they are considered to deviate from social norms and are seen as criminals. This is a vulnerable group. The aim of this research is to see how vulnerable groups of women at the Class IIA Women's Correctional Institution in Kerobokan, Bali, can turn stigma into opportunities. This study uses qualitative methodology and is designed as a case study. Data were collected thru limited observations, in-depth interviews, and documentation research involving female inmates, prison officers, and supporters of the rehabilitation program. To identify patterns of rehabilitation strategies and experiences of stigma transformation, data analysis was conducted thematically. The research results show that inmates experience stigma both personally and socially, but it can be transformed thru a rehabilitation approach that includes the development of useful skills, strengthening their identity, and institutional support from the prison environment. This strategy enhances the confidence and readiness of inmates for life after incarceration. This research concludes that the elimination of stigma on female inmates is a strategic process influenced by a holistic and contextual rehabilitation approach. The results provide an empirical basis for creating more inclusive and socially reintegrative policies for female inmates.